DAYA HAMBAT OPTIMUM KOMBINASI EKSTRAK Eichhornia crassipes DAN Pistia stratiotes TERHADAP Candida albicans - Putri, Putri; Budiarti, Lia Yulia; Kaidah, Siti (Homeostasis, 2023)
Candida albicans (C. albicans) is an opportunistic pathogenic fungus that causes candidiasis. Eichhornia crassipes (EC) and Pistia stratiotes (PS) are known to contain antifungal bioactive compounds. This study aims to analyze the effect of the combination of EC and PS extracts on C. albicans, which produces optimum inhibition. The design of this study used a post-test only with in-vitro control group design. Combination treatment of EC and PE extracts 25%, 50%, 75%, and 100% (ratio 1:1), control of ketoconazole and 10% DMSO. Data analysis used Duncan's One-way Anova and post-hoc tests. The diameter of the inhibition zone resulting from the EC+PS combination treatment was moderate (8,63 ± 0,50 mm) to very strong (21,12 ± 0,002 mm). There was a significantly different effect between the EC+PS combination treatments (p>0,05). The inhibition zone in the EC100%+PS100% combination treatment was the largest and the effect was equivalent to that of ketoconazole (p<0,05). In conclusion, the EC+PS combination treatment produced varying optimum inhibition against C. albicans which was in line with the concentration of the EC+PS combination.